1994
DOI: 10.1097/00006250-199406000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hemorrhage at Cesarean Delivery

Abstract: Patients undergoing cesarean delivery who have factors exposing them to increased risk of hemorrhage can be identified prospectively. These women will benefit greatly from extended preoperative counseling when possible, effective utilization of blood bank technology through type and cross-match requests, and preventive measures during abdominal delivery to minimize blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 0 publications
1
46
3
Order By: Relevance
“…Postpartum hemorrhage associated with obesity was described by Bowers & Cohen 4 and with greater weight gain by Magann et al 10 The study data showed no such risk for obesity and as such are inconsistent with Naef et al 14 findings, which characterized obesity as a risk factor. Moreover, it was found no previous reports stratifying risk of hemorrhage by route of delivery and reporting that the association of hemorrhage with greater weight gain is restricted to those with vaginal delivery.…”
Section: Discussionmentioning
confidence: 85%
“…Postpartum hemorrhage associated with obesity was described by Bowers & Cohen 4 and with greater weight gain by Magann et al 10 The study data showed no such risk for obesity and as such are inconsistent with Naef et al 14 findings, which characterized obesity as a risk factor. Moreover, it was found no previous reports stratifying risk of hemorrhage by route of delivery and reporting that the association of hemorrhage with greater weight gain is restricted to those with vaginal delivery.…”
Section: Discussionmentioning
confidence: 85%
“…Obstetric haemorrhage can occur in association with operative abdominal delivery 3 . In a recent investigation at our institution, we discovered that 8% of our caesarean deliveries are accompanied by blood loss in excess of 1500mL and/or a drop in the haematocrit of 10% 4 . Several techniques have been proposed to reduce blood loss at operative abdominal delivery, including placental management (spontaneous compared with manual extraction) and in situ uterine incision repair compared with exteriorisation 5 -7 .…”
Section: Introductionmentioning
confidence: 94%
“…Depending on the severity of blood loss anaemic patients may present an increased morbidity, including cardiovascular symptoms, dizziness, fatigue, infections and lactation problems [1][2][3].…”
Section: Introductionmentioning
confidence: 99%